Process and temperature performance of a CMOS beta-multiplier voltage reference - Song Liu; Baker, R.J. (Circuits and Systems; Proceedings: Midwest Symposium on Circuits and Systems, 1998)
The beta multiplier voltage reference (BMVR) is discussed as a direct replacement for the bandgap voltage reference in a CMOS process especially when substrate current is a concern. Performance of the BMVR with regard to temperature and process variations is covered. Experimental results from a 2-micron MOSIS test chip indicate that the BMVR can be tuned to within 10 mV of a desired value while maintaining a temperature coefficient below 1000 ppm/C and a supply sensitivity under 50 mV/V.